Anemia and child malnutrition in rural zones: impact of a comprehensive intervention at the community level - Reyes Narvaez, Silvia Elizabet (2019)
The objective of this research was to determine the impact of an intervention program at community level in the reduction of anemia and child malnutrition. Applied research of quasi-experimental design with pretest and posttest of a single group. The sample size was 300 children under 5 years old selected through a probabilistic sampling in 4 population centers of the district of Barranca: Santa. Elena, Pampa San Alejo, Vinto and Araya. Data were obtained through the anthropometric assessment and hemoglobin examination with the portable hemoglobinometer, then a home intervention program was applied to children and parents and included educational talks and demonstration sessions related to anemia and malnutrition. Likewise, educational programs were developed to the community with massive campaigns that included playful games and group workshops to reinforce the knowledge provided at home. It was observed that before the intervention 145 children were anemic and after the intervention only 46 children had anemia, in the same way 40 children were malnourished and after the intervention only 31 children presented malnutrition. It is concluded that the program of intervention at the community level has a positive impact on the reduction of anemia and infant malnutrition, test of hypothesis with the Mc Nemar test, (P = 0.000 <0.05 for anemia) and (value = 0.004 <0.05 for malnutrition).